The practice of life cycle cost in Malaysia construction industry: a review / Wan Nur Hamizah Wan Hassan, Norhanim Zakaria and Muhammad Azzam Ismail - Wan Hassan, Wan Nur Hamizah; Norhanim, Zakaria; Ismail, Muhammad Azzam (Faculty of Architecture, Planning & Surveying and UiTM Press, 2014)
Life cycle cost (LCC) is a concept and practices that seem ambiguously understood in the construction industry in Malaysia. This paper reports on the initial phase of the study and its results. The initial study was carried out through the literature review on LCC in general and focuses on the application of LCC in Malaysia. The main focus on this study is to identify the current practice and the enhancement of the LCC in construction projects. There are six (6) practitioners in construction industry that been interviewed in related to the research study. The outcome of this research shows that most of the practitioners are aware on the term and concepts of the LCC but did not apply in their construction projects. There are few challenges are listed and their opinions on the solution to solve the lack of application LCC. The paper also identifies the elements cost and evaluation method used in developing the LCC plan.